The Spanish Civil War and the British labour movement - Buchanan, Tom 1960- (Cambridge University Press, 1991)
This book draws on a mass of documentary material to provide a major reinterpretation of British labour's response to the Spanish Civil War. It challenges the view that the labour leadership ' betrayed' the Spanish Republic, and that this polarised the movement along 'left' versus 'right' lines. Instead, it argues that the overriding concern of the major leaders was to defend labour's institutional interests against the political destabilisation caused by the conflict, rather than to defend Spanish democracy. Although the main advocates of this position were trade union leaders associated with the labour right such as Walter Citrine and Ernest Bevin, the book argues that their dominance reflected the centrality of the trade unions to labour movement decision-making rather than the abuse of union power to achieve political goals
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Trades Union Congress / Political activity / History / 20th century; Labour Party (Great Britain) / History / 20th century; Geschichte 1900-2000; Geschichte; Gewerkschaft; Spanischer Bürgerkrieg (1936-1939); Public opinion / Great Britain / History / 20th century; Labor unions / Political activity / Great Britain / History / 20th century; Working class / Political activity / Great Britain / History / 20th century; Arbeiterbewegung; Spanischer Bürgerkrieg -- 1936-1939; Großbritannien; Spanien; Spain / History / Civil War, 1936-1939 / Public opinion; Spain / History / Civil War, 1936-1939 / Participation, British; Spain / Relations / Great Britain; Great Britain / Relations / Spain; Hochschulschrift